CNS Prophylaxis: How Far Is Routine Practice From the Guidelines? Focus on a Nationwide Survey by the Fondazione Italiana Linfomi (FIL) - Gini, Guido; Di Rocco, Alice; Nassi, Luca; Arcari, Annalisa; Tisi, Maria Chiara; Loseto, Giacomo; Olivieri, Attilio; Gentile, Massimo; Annibali, Ombretta; Cabras, Maria Giuseppina; Chiappella, Annalisa; Rusconi, Chiara; et al. (Frontiers in Oncology, 2021)
Central nervous system (CNS) involvement is a rare but almost fatal complication of diffuse large B-cell lymphoma (DLBCL). There is no consensus on the optimal CNS risk model and prophylaxis treatment. We conducted in all FIL centers a web-based survey, focused on algorithms used in routine practice to identify DLBCL patients at high CNS risk involvement. We collect the centers’ characteristics and the disease incidence, the CNS risk assessment and the diagnostic method and finally the type of prophylaxis used. Sixty-three out of 110 centers fulfilled the survey. 46% treat >30 DLBCL/years (yrs) and 40% 11-30 cases/yrs. In the last 5 yrs, 6% of centers reported >10 DLBCL with CNS and systemic localization at the diagnosis, 30% reported 4-10 cases and 48% reported <4 cases. Concerning the identification of meningeal/CNS disease, cerebrospinal fluid (CSF) was performed only in patients with CNS-IPI >4 in 21% of centers, whereas in 56% of centers this procedure was performed in patients with either CNS-IPI >4 or with high-risk extranodal site. Patients with double\triple hit lymphoma, with double/triple + ABC and double expresser lymphomas were considered at high CNS risk in 44%, 49% and 49% of centers, respectively. CNS disease status was assessed by CSF evaluation and imaging in 79% and 73% of centers, respectively. CNS prophylaxis consisted of intrathecal Methotrxate (MTX) in 58% of centers and in HD-MTX (1.5 to 3 gr/sqm) in 40% of centers. This survey shows real-life practice and the differences in diagnosis and prophylaxis of CNS in DLBCL patients.